Matrix-isolation FT-IR spectra and theoretical study of dimethyl sulfate - Borba, Ana (2005)
The preferred conformations of dimethyl sulfate and their vibrational spectra were studied by matrix-isolation FT-IR spectroscopy and theoretical methods (DFT and MP2, with basis sets of different sizes, including the quadruple-zeta, aug-cc-pVQZ basis). Conformer GG (of C2 symmetry and exhibiting OSOC dihedral angles of 74.3°) was found to be the most stable conformer in both the gaseous phase and isolated in argon. Upon annealing of the matrix, the less stable observed conformer (GT; with C1 symmetry) quickly converts to the GG conformer, with the resulting species being embedded in a matrix-cage which corresponds to the most stable matrix-site for GG form. The highest energy TT conformer, which was assumed to be the most stable conformer in previous studies, is predicted by the calculations to have a relative energy of ca. 10 kJ mol-1 and was not observed in the spectra of the matrix-isolated compound.